TRANSFORMATIONAL LEADERSHIP IN QUALITY ORGANIZATIONAL MANAGEMENT - Sholihah, Imroatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses transformational leadership which is the main foundation for organizations in achieving excellence and success. The research method used is field research with a qualitative approach, involving holistic observation of individuals. The research location was carried out at the Nurul Jadid Paiton Islamic Boarding School, Paiton, Probolinggo in 2024. The main aim of this research is to contribute to the understanding of the role of transformational leadership in creating a quality organizational culture and improving team performance in religious organizational environments. The research results show that transformational leadership has a significant positive influence in forming a quality organizational culture. Open communication, regular evaluation, and building member involvement are key elements in the successful implementation of transformational leadership.